Advancements in Dental Implantology: A Comprehensive Review - Sabah Hamzah Hawsawi; Asmaa Bakr Hafiz; Samah Ahmad Gassim; Bayan Abdulkarim Qashqari; Halimah Othman Abbas; Reem Aali Alqurashi; Habibah Othman Barnawi; Haya Soluman Almuallad; Maram Saad Altambakti (International Journal of Medical Toxicology and Legal Medicine, 2024)
Dental implantology is one of the fields that has grown tremendously over the past few decades, thereby improving the health of patients undergoing oral surgical procedures. This systematic review aims to evaluate the research progress in dental implantology based on the secondary data collected and assessed. Therefore, through the analysis of the available literature in the form of peer-reviewed articles, clinical trials, and reports from the industry, the study presents a review of implant materials, techniques, and technologies that have been considered in the treatment over the recent years. Some specialized aspects include new material science and research as well as the clinical application of advanced biomaterials; digital dentistry 3D printing technology integrated with customized implants; and bioengineering as a means of improving implant stability as well as post-implant recovery. Moreover, the review discusses the patient’s quality of life, complications, and overall success over time and among different groups. The study reveals significant enhancements in terms of procedural organization, patient satisfaction, and functional gains that demonstrate the importance of continued advancement in dental implantology. Future recommendations include the continuation of interdisciplinary research and additional longitudinal studies to support and build on these developments.